An alternative proof of logarithmically improved Beale–Kato–Majda type extension criteria for smooth solutions to the Navier–Stokes equations. (November 2018) - Nakao, Kohei; Taniuchi, Yasushi
Abstract: We give an alternative proof of a logarithmically improved Beale–Kato–Majda type extension criterion for smooth solutions to the Navier–Stokes equations in the whole space, which was shown by Fan et al. (2011). By our method, we can also establish a similar criterion to the above in case of the half space, bounded domains and exterior domains.